2003
DOI: 10.1089/109264203766207663
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Outcome Analysis of Bilateral versus Unilateral Endoscopic Extraperitoneal Inguinal Hernioplastics

Abstract: The postoperative recovery and morbidity of patients who underwent bilateral TEP were equivalent to those who underwent unilateral TEP. Simultaneous bilateral TEP is safe and advantageous in patients with from bilateral inguinal hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
6
18
0
Order By: Relevance
“…In this study the incidence of OCH was 26% (13/50), and left-sided hernias were 17.5% more likely to have an OCH than were rightsided hernias. This seems to be consistent with existing literature regarding the higher incidence of OCH on the opposite side in left-sided hernias [18]. The reason postulated for the higher incidence of OCH on the right in hernias of the left side could be attributed to embryological development of the processus vaginalis by which the left processus is the one that obliterates first.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study the incidence of OCH was 26% (13/50), and left-sided hernias were 17.5% more likely to have an OCH than were rightsided hernias. This seems to be consistent with existing literature regarding the higher incidence of OCH on the opposite side in left-sided hernias [18]. The reason postulated for the higher incidence of OCH on the right in hernias of the left side could be attributed to embryological development of the processus vaginalis by which the left processus is the one that obliterates first.…”
Section: Discussionsupporting
confidence: 92%
“…Among the 13 contralateral cases (OCH), 6/16 were on the right side in left-sided hernias and 7/34 were on the left in right-sided hernias. The incidence of OCH in our study falls well within the previously reported incidence of OCH [9,15,16,18]. However no comparison was made in previous studies with respect to operative time and the incidence of complications in true unilateral cases versus those in which a contralateral OCH was discovered.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The duration of surgery in the study of Lau et al [18] (unilateral, 64 min vs. bilateral, 97 min) was comparable with that in our study. The recovery time, mean LOS (unilateral, 1.5 days vs. bilateral, 1.7 days), and incidence of postoperative general complications and postoperative surgical complications did not differ significantly between the two groups.…”
Section: Discussionsupporting
confidence: 90%
“…These data correspond to findings from a much smaller study reported by Lau et al [18], in which 103 patients undergoing bilateral TEP for inguinal hernia were prospectively investigated during 3 years and compared with an age-matched cohort of patients who underwent unilateral TEP during the same period. The duration of surgery in the study of Lau et al [18] (unilateral, 64 min vs. bilateral, 97 min) was comparable with that in our study.…”
Section: Discussionsupporting
confidence: 87%